Analiza kursów walut w transakcjach hedgingowych - podejście prognostyczne - Jędrzejczyk, Marcin (The Analysis of the Exchange Rates in Hedging Transactions - the Prognostical Approach, 2005)
The paper presents the practical approach to the hedging transactions. The conducted analysis is based on the exchange rate theory and productivity ratio. The prospective aspect of the research constitutes a fundamental premise to the process of decision making concerned with foreign currencies transactions. The main attention should be paid to the determinants of the exchange rate shaping, which can allow conducting the forecast in the assumed time horizon. Thus, the accurate forecast is treated as the necessary condition to engage into hedging transactions, which can successfully protect from exchange rate fluctuation risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 192-202